Konsekuensi Hukum atas Kepemilikan Saham Pemda Sumbar di PT Bank Nagari - Putri, Diva Dezi; Azheri, Busyra; Rosari, Anton (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2024)
Based on Article 399 paragraph (1) of Law Number 23 of 2014 concerning Regional Government jo Article 5 paragraph (1) of Government Regulation Number 54 of 2017 concerning Regionally Owned Enterprises states that one of the requirements for BUMD in the form of Perseroda is the existence of share ownership by one of the shareholder regions with a minimum percentage of 51% (fiftyone percent). As of December 31, 2023, the highest percentage of share ownership in PT Bank Nagari is owned by the West Sumatra Provincial Government, which is 32.51% (thirtytwo point fifty one percent). The percentage of shares owned by the West Sumatra Provincial Government as the Highest Shareholder still does not meet the provisions of the regulations that make the status of PT Bank Nagari as Perseroda. The difference in practice that occurs at PT Bank Nagari with the provisions of the laws and regulations needs to be studied. This study discusses is the legal consequences if the percentage of share ownership is not fulfilled by the Regional Government of West Sumatra Province as the controlling shareholder in PT Bank Nagari as a Regional Company. The research method uses a Juridical-Normative problem approach, which is supported by empirical data. The conclusion of this study is the consequences of the unfulfilled share ownership are not regulated by any laws and regulations. However, even though there are no firm consequences, the status of PT Bank Nagari as a state-owned company in the form of Perseroda does not obtain legal certainty.